(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The human rights are essential for the growth and the development of every human being including the children. At present, the violations of children’s rights become the serious issue. Many children are working in the worst forms of labour like bondage, semi-slavery, prostitution and so on. They are depriving their basic rights such as right to education, right to development, right to survive and even right to childhood. Consequently, they are becoming victim of maltreatment, child marriage, kidnapping and abduction, immoral trafficking and child rape or sexual abused etc. The paper is trying to analyses the various aspects of child labour. Further, the study finds out the roots causes of the problems.